Resource use efficiency and constraints in cultivation of maize in Haryana - PAWAR, NEERAJ; SUMIT, SUMIT; MALIK, D P (The Indian Journal of Agricultural Sciences, 2021)
The study was carried out during 2019 to determine the resource use efficiency and constraints faced in kharif maize growers in Karnal and Yamunanagar districts of Haryana. The experiment was conducted by surveying 60 maize cultivators selecting 30 respondents from each i.e. Karnal and Yamunanagar districts. Maize growers were personally interacted to extract relevant information. Cobb- Douglas production function was used to determine the resource use efficiency of maize cultivation to find out the most significant factor which influences the respondent; Henry Garrett's (1969) ranking technique was used. For optimal allocation of resource, it was observed that all the inputs in both the districts were less than unity, which indicates that all these inputs were over utilized in the respective district. It reflects that all the inputs were over utilized and use of these inputs needs to be curtailed to attain higher returns. Major constraints were watch and ward required to protect the crop from stray animals, lack of availability of suitable machines for threshing of maize, lack of availability of maize dryers and lack of availability of quality seed of recommended maize hybrids as specified by the maize growers.